Learning alliances in software industry. - Ng, Mian Hui. (2008)
In this research, the author looks into how strategic alliances in helping local firms gain the competitive advantage (obtained through learning) that will prepare them for the turn of the century. We examine how learning among the alliances takes place and the level of their learning.